A global biodiversity observing system to unite monitoring and guide action - Luers, Amy (Nature Ecology and Evolution, 2023)
The rate and extent of global biodiversity change is surpassing our ability to measure, monitor and forecast trends. We propose an interconnected worldwide system of observation networks — a global biodiversity observing system (GBiOS) — to coordinate monitoring worldwide and inform action to reach international biodiversity targets.